PERMAINAN ANAK YANG MENGGUNAKAN NYANYIAN (Kajian Wilayah: Jakarta, Depok, Bogor, Tangerang, dan Bekasi) - Adi Sam, Tuti Tarwiyah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
The study is about an almost extinct form of culture that is traditional game with song. The objective of the study is to identify/gather children game in order to preserve traditional game, specifically Betawian children game with song. Qualitative method is used as the approach of the study, focusing on ethnographic research. The study takes place in DKI Jakarta and its surroundings, especially Jakarta suburbs, i.e. Depok, Bogor, Tangerang, and Bekasi. The data analysis is done from the beginning and throughout the process of the study, employing qualitativedata analysis method proposed by Miles and Huberman. Some findings of the study are: One, Betawian children games consist of games with equipment and games with song. Two, there are three games using songs, they are (1). Hompimpah/Gambreng, (2). Tung Keripik, (3). Dang- Dang Tut. Three, five games for children below three years old using song sang by parents: (1). Klung Neng Nang, (2). Laa ilaaha illallaah, (3). Gong Anggong, (4). Cang Uncang Angge, dan (5). Jeg Ujeg Gantil. Four, songs/games with spell, they are: (1). Jeg Ujeg Gantil, (2). Uruk- Uruk Ujan, (3). Pang Numpang, (4). Cengcorang, (5). Rep Sirep, dan (6). Sep Asep. Five, 13 Betawian children games with song: (1) Cici Putri, (2) Wak – Wak Gung, (3) Keripik Jengkol, (4) Pung–Pung Balong, (5) Nenek Gerondong/ Tug–Tug Gene/Tug Tug Ubi, (6) Sim Terima Kasim, (7) Bokeran, (8) Umpet Batu/Titibeni, (9) Serondeng Kacang Tanah, (10) Orang Kaya Orang Miskin, (11) Deng Endengan/Sirih Tampin/Sirih Kuning, (12). Baris Tempe- Tempe, dan (13). Caca Gulali/Dung Dung Clok. Six, there is an appropriateness of children songs with game with the theory of classic games. Seven, there are eight games that are rooted and developed from Betawian children game with song. Kata kunci: permainan anak, , nyanyian